1923 the crisis of German democracy in the year of Hitler's putsch - Jones, Mark 1981- (Basic Books, 2023)
In 1923, the Weimar Republic faced a series of crises, including foreign occupation of its industrial heartland, rampant inflation, radical violence, and finally Hitler’s infamous "beer hall putsch." Fanning the flames of anti-government and anti-Semitic sentiment, the Nazis tried to violently seize power in Munich, only failing after they were abandoned by like-minded conservatives. In 1923, historian Mark William Jones draws on new research to offer a revealing portrait of German politics and society in this turbulent year. Tracing Hitler’s early rise, Jones reveals how political pragmatism and unprecedented international cooperation with the West brought Germany out of its crisis year. Although Germany would succumb to tyranny a decade later, the story of the republic’s survival in 1923 offers essential lessons to anyone concerned about the future of democracy today.
Keywords: Hitler, Adolf -- 1889-1945; Geschichte 1923; Hitlerputsch; Deutschland